2016
DOI: 10.1371/journal.pone.0157110
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Quality of Maternal and Newborn Care in Developing Countries Using Demographic and Health Surveys

Abstract: BackgroundOne of the greatest obstacles facing efforts to address quality of care in low and middle income countries is the absence of relevant and reliable data. This article proposes a methodology for creating a single “Quality Index” (QI) representing quality of maternal and neonatal health care based upon data collected as part of the Demographic and Health Survey (DHS) program.MethodsUsing the 2012 Indonesian Demographic and Health Survey dataset, indicators of quality of care were identified based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…Only 29.4% of maternal deaths occurred at the home. Several studies have suggested that poor quality of maternal care at health facilities in Indonesia contributes to high maternal mortality . A study in Papua province suggests poor quality and delays in receiving appropriate care at facilities are the major causes of maternal mortality …”
Section: Introductionmentioning
confidence: 99%
“…Only 29.4% of maternal deaths occurred at the home. Several studies have suggested that poor quality of maternal care at health facilities in Indonesia contributes to high maternal mortality . A study in Papua province suggests poor quality and delays in receiving appropriate care at facilities are the major causes of maternal mortality …”
Section: Introductionmentioning
confidence: 99%
“…For instance, Demographic and Health Surveys (DHS) do not collect information on patient satisfaction and safety or health inputs or system efficiency. 22) To overcome this data constraint, prior studies have often used caesarean and episiotomy rates, 23) neonatal near-miss events (i.e., newborn infants presenting selected markers of severity and surviving the first neonatal week), 24) and maternal mortality as proxy indicators for quality of care. Another recent study used principal components analysis based techniques to quantify variation in quality of care using core DHS indicators for Indonesia and found disparities by wealth and geographical regions.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study used principal components analysis based techniques to quantify variation in quality of care using core DHS indicators for Indonesia and found disparities by wealth and geographical regions. 22) We offer a fairly new approach to derive contextual provider quality indicators and assess their relative importance along with individual utilization of ANC and SBA in India using multilevel framework. This study uses the latest nationally representative data from India to first create indicators for district and state provider quality based on residuals deviating from the ecological associations between ANC (and SBA) rate and prevalence of neonatal, infant, and under-five mortality at each respective level.…”
Section: Introductionmentioning
confidence: 99%
“…13 Several authors have proposed different types of quality indicators for ANC. 3,[5][6][7][8]12,[14][15][16][17] Some have proposed binary indicators (e.g. good vs. poor quality) [5][6][7] or categorical classifications (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In most studies, good quality in ANC was defined as having received all or most of the components considered. 5,6,15,16 Another strategy to create a "quality index" was proposed by Dettrick et al using data from Indonesia, 17 by principal components analysis to derive weights and calculate a score.…”
Section: Introductionmentioning
confidence: 99%